ANALISIS PENERAPAN DIGITAL MARKETING TERHADAP MINAT BELI KONSUMEN PADA TOKO JAREJEKU DI KABUPATEN SIDENRENG RAPPANG PROVINSI SULAWESI SELATAN - Syahlan, Zakia; Ramlan, Pratiwi; Syafaruddin, Andi Riska Andreani (LP2M Universitas Bina Bangsa, 2025)
Digital marketing is a type of marketing whose use is digital. Marketing techniques that were initially only offline-based, are now shifting to the digital era (online). Digital marketing can be done either through the web, e-mail or social media. With digital marketing, it will make it easier for business actors to market their products. The purpose of this study is to analyze the application of digital marketing (Tiktok social media) to consumers' buying interest in Jarejeku Shop. The method used is a quantitative research method with data collection techniques through observation, interviews, and questionnaires (Likert scale). The data analysis technique uses simple linear regression. The population in this study includes consumers of Toko Jarejeku with a sample of 96 people. The results of the study show that the results of the t-test are obtained that the Digital Marketing (X) variable has a significant effect on Consumer Buying Interest (Y) in Jarejeku stores